Responsabilidade civil dos provedores de internet pelo conteúdo gerado por terceiro - Santos, Lucas Vicente Romero Rodrigues Frias dos (2015)
In this paper we face the issue of Internet service provider liability for content generated by third parties. With the enactment of Law 12,965 of April 23, 2014, known as Civil Marco of the Internet, doctrinal definitions were modified and new concepts were integrated into the legal system. And so it was with the liability of internet service providers. This tune and upon the a sandy soil of so young a subject, we will seek to form a logical system of the liability of internet service providers, having as main objective the fair and systematic application of the law, resulting in the effective protection of the user, without improperly burdening the providers